Seasonal dynamics of cardiovascular events in the Russian Federation - N. V. Kuzmenko; M. M. Galagudza; A. A. Fedorenko; N. E. Zvartau; E. V. Shlyakhto (Российский кардиологический журнал)
Aim. To study the seasonal dynamics of cardiovascular events (CVE) in the Russian Federation (RF) using medical and statistical data for the period 2016-2019, and also to establish an association of CVE risk with meteorological conditions.Material and methods. We used data on hospitalizations for 2016-2019 for hemorrhagic stroke (HS), ischemic stroke (IS), myocardial infarction (MI), and acute coronary syndrome (ACS).Results. Data analysis showed that the maximum number of HSs occurred in winter and spring, and the minimum in summer. The maximum number of ISs was recorded in spring and summer, while the minimum in winter and autumn. ACS occurred more often in winter and spring, MI — more often in spring. ACS was accompanied by MI in 44% of cases. In winter, the probability of HS increased with decreasing latitude.In summer, the risk of HS and IS was greater at lower air temperatures. In summer, the probability of IS and MI was associated with lower values of atmospheric pressure and partial density of oxygen (ρO2). In winter, the risk of IS increased at highr atmospheric pressure values. No convincing evidence was obtained of the influence of geomagnetic activity on the seasonal dynamics of the CVEs either throughout the Russian Federation or in the circumpolar regions.Conclusion. As a result, meteorological conditions influence the seasonal risk of CVEs. A decrease in ρO2 in summer significantly increases the CVE risk associated with ischemia, which should be taken into account when preventing CVEs.